Respuesta :
Answer:
To find the value of x
1. Solve what it is in the parentheses
2. Combine like numbers on each side of the equation if is possible
3. Subtract 12 on both sides of the equation
4. Subtract 3x on both sides of the equation
5. Divide by 6 both sides of the equation
Step-by-step explanation:
9x + 12 = 3(x-8)
9x + 12 = 3x -24
-12 -12
9x = 3x -36
-3x -3x
6x = -36
6 6
x = -6
The equation that represent the first step that should be required is 9x + 12 = 3x -24.
Calculation of an equation:
Since the equation is
9x + 12 = 3(x-8)
So
9x + 12 = 3x -24
6x = -36
x = -6
So based on this, we can say that The equation that represent the first step that should be required is 9x + 12 = 3x -24.
Learn more about an equation here: https://brainly.com/question/17599700